Obesity Indicators and C-Reactive Protein in Indonesian Adults (More than Equal to 40 Years Old): The Indonesian Family Life Survey 5 - Mahwati, Yeni; Nurrika, Dieta (UI Scholars Hub, 2020)
C-reactive protein (CRP) is the best clinical marker for systemic inflammation. Obesity is associated with increased CRP levels. Systemic inflammation is present before morbidity occurs. Research reveals that the identification of obesity indicators and CRP levels is limited among Indonesians. The present study investigated the associations between obesity indicators (body mass index [BMI], waist circumference [WC], waist-to-hip ratio [WHR], waist-to-height ratio [WHtR]) and CRP levels among Indonesian adults. This cross-sectional study based on Indonesian Family Life Survey-5 2014–2015 was conducted among 3,386 adults (≥ 40 years) living in 13 provinces in Indonesia during the study period. All data were collected in 2014. Multiple logistic regression was used to estimate the odds ratio (ORs) and 95% confidence interval (95% CIs) for hs-CRP levels on obesity indicators by using underweight (BMI) and normal (WC, WHR, and WHtR) as references. Our multivariable logistic regression analysis indicated that respondents with increased WHR (OR: 1.278, 95% CI: 1.005–1.625, p-value < 0.001) were more likely to have high-risk hs-CRP levels than those with normal WHR. Compared with respondents with normal WHtR, those with increased WHtR were found associated with high-risk hs-CRP levels (OR: 1.980, 95% CI: 1.544–2.541, p-value < 0.001). Therefore, WHR and WHtR can predict central obesity, which is associated with hs-CRP levels.